REGULASI EMOSI PADA GURU DITINJAU DARI STATUS PERNIKAHAN - MIRA ARIYANI; SHARA ZAKIA NISSA (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2016)
Emotion regulation is an individual process based on an individual's knowledge of emotions and emotional management, and expressive behavior, in which the process can be executed consciously in order to achieve goals, especially for social purposes. The study aims to find out the difference of emotional regulation in teacher context in terms of marital status (single, married, and divorced). This research uses quantitative method, with 138 subjects. The instrument used is an adoption of Emotion Regulation Questionnaire/ERQ (Gross & John, 2003). ERQ measures two aspects that are specific strategies of emotional regulation, namely: reappraisal and suppression.Hypothesis testing uses one-way anova. The results showed that there are significant differences of reappraisal emotion regulation in single, married, and divorced teachers (p < Î± ; 0,034 < 0,05). Whereas suppression emotion regulation is no significant difference in single, married, and divorced teachers (p > Î± ; 0,171 > 0,05).